Perubahan Beberapa Sifat Kimia Tanah Lahan Pasang Surut akibat Budidaya Tanaman Jagung (Zea mays L.) - Jeannie Valinda Auditha; Dedik Budianta; Dwi Setyawan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Auditha JV, Budianta D, Setyawan D. 2019. Changes in some chemical soil properties of tidal land due to maize cultivation (Zea mays L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 101-110. Palembang: Unsri Press.Soil fertility of tidal land is relatively low, thus fertilizer and lime is needed to support plant nutrient needs, but tidal land planted with maize plants will produce resdies in the soil after harvest. This study aims to examine changes ins some of chemicalproperties of tidal land due to corn cultivation. This field research was conducted in Augest to Decemver 2018 on typology B tidal land ind Mulia Sari Village, Tanjung Lago District, Banyasin District.this study used a Factorial Randomized Group Design consisting of 2 factors. Factor 1 is fertilizer derived from location spesific and fertilizer from recommendation by Balitbang Pertanian Sumsel. Whereas for factor 2, namely dose of lime at the rate of 1,932 tons ha-1, at 3,864 tons ha-1, and at 5,796 tons ha-1 respectively. Each treatment was repeated 3 times to obtain 18 plots. The results of this study indicated that corn cultivation can reduce soil pH and N-total, but at the highest lime dose at the rate of 5,796 tons ha-1 can increase soil pH by 0.05 units. Maize cultivation can also increase 2.22% C-organic, P-available (13.95 mg kg-1), Cation Exchange Capacity (CEC) as much as 1.42 cmol (+) kg-1, K-dd 0 , 98 cmol (+) kg-1, Ca-dd 0.55 cmol (+) kg-1, Mg-dd 0.46 cmol(+) kg-1, while the value of Al-dd increased due to liming at 1,932 tons ha-1and 3,864 tons ha-1 but decreased by 0,36 cmol(+) kg-1 in lime at the rate of 5,796 tons ha-1. The conclusion from this study is that corn cultivation can improve some soil chemical properties.Keywords: fertilizer, lime, maize cultivation